A brief alcohol intervention during smoking cessation treatment in daily cigarette smokers: A pilot randomized controlled trial - Yee Tak Derek Cheung; Tin Shun Titan Mak; Tzu Tsun Luk; Kam-wing Joe Ching; Nga-ting Grace Wong; Ching Han Helen Chan; Man Ping Wang; Tai Hing Lam (Scientific Reports, 2024)
Abstract Alcohol use attenuates successful smoking cessation. We examined the feasibility, acceptability, and preliminary efficacy of a brief alcohol intervention in smokers. In this two-arm, assessor-blinded randomized controlled trial, we randomized 100 daily smokers (82.0% male, mean age = 43.7 years) with past-year alcohol use in smoking cessation clinics. Both intervention (n = 51) and control (n = 49) groups received conventional smoking cessation treatment, the intervention group additionally received a brief alcohol intervention. Primary outcome was biochemically validated tobacco abstinence at 2 months. Secondary outcomes included Alcohol Use Disorders Identification Test (AUDIT) scores, self-reported past 7-day alcohol consumption in alcohol units, feasibility, and acceptability scores at 2 months. By intention-to-treat, the intervention group showed higher validated abstinence (11.8% vs. 10.2%, Risk Ratio = 1.15, 95%CI = 0.38–3.53), lower AUDIT score (5.3 vs. 6.5), and lower alcohol consumption (5.6 vs. 7.1) than the control group, but the differences were not significant. Overall, the feasibility was high (4.2/5.0), and the acceptability was modest (5.0/7.0). In all participants, reduction in smoking relapse risk due to alcohol use from baseline to 2-month follow-up was associated with higher biochemically validated abstinence (Adjusted odds ratio: 1.55, 95% CI = 1.05–2.28). Our brief alcohol intervention is feasible, acceptable, and potentially efficacious to promote tobacco abstinence and alcohol reduction.